2007
DOI: 10.1897/06-519r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic toxicity of glyphosate compounds to glochidia and juveniles of Lampsilis siliquoidea (unionidae)

Abstract: Native freshwater mussels (family Unionidae) are among the most imperiled faunal groups in the world. Factors contributing to the decline of mussel populations likely include pesticides and other aquatic contaminants; however, there is a paucity of data regarding the toxicity of even the most globally distributed pesticides, including glyphosate, to mussels. Therefore, the toxicity of several forms of glyphosate, its formulations, and a surfactant (MON 0818) used in several glyphosate formulations was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 35 publications
1
52
0
Order By: Relevance
“…However, many other endpoints could be explored, and some may provide more insight into effects from chronic exposure. Relevant toxicological endpoints in sublethal studies of freshwater mussel sensitivity to other contaminants that may be applied in future fluridone and endothall studies include growth (in juveniles, Bringolf et al 2007;Wang et al 2007Wang et al , 2011Wang et al , 2013, glochidial metamorphosis success (Hazelton et al 2013), female mantle lure display (Bringolf et al 2010;Hazelton et al 2013;Leonard 2013), hemolymph and tissue analysis (Archambault et al 2013;Leonard 2013), movement and burrowing (Flynn & Spellman 2009;Archambault et al 2013;Hazelton et al 2014), and metabolomics (Leonard 2013). We attempted to evaluate female mantle lure display in our experiment, but we had few females per replicate, thus there was insufficient statistical power to make sound inferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many other endpoints could be explored, and some may provide more insight into effects from chronic exposure. Relevant toxicological endpoints in sublethal studies of freshwater mussel sensitivity to other contaminants that may be applied in future fluridone and endothall studies include growth (in juveniles, Bringolf et al 2007;Wang et al 2007Wang et al , 2011Wang et al , 2013, glochidial metamorphosis success (Hazelton et al 2013), female mantle lure display (Bringolf et al 2010;Hazelton et al 2013;Leonard 2013), hemolymph and tissue analysis (Archambault et al 2013;Leonard 2013), movement and burrowing (Flynn & Spellman 2009;Archambault et al 2013;Hazelton et al 2014), and metabolomics (Leonard 2013). We attempted to evaluate female mantle lure display in our experiment, but we had few females per replicate, thus there was insufficient statistical power to make sound inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, of the 703 freshwater gastropod species in USA and Canada, 278 (40%) are federally listed as endangered and >74% are considered imperilled (Johnson et al 2013). Moreover, non-pulmonate snails and the early life stages of freshwater mussels are among the most sensitive aquatic organisms to several contaminants (e.g., atrazine, carbaryl (Conners & Black 2004); copper, ammonia (Besser et al 2009)), and glyphosate-based chemicals which are among the most widely used herbicides (Bringolf et al 2007). Potential risks of specific aquatic herbicides to freshwater molluscs should be assessed and balanced appropriately against the significant biological threat posed by invasive aquatic weeds like hydrilla.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have already reported that non-ionic surfactants interacting with plant cuticles are highly water soluble (Hess and Foy, 2000) and can enter aquatic ecosystems after heavy rain episodes. The effects of glyphosate on aquatic organisms are generally considered to be moderate (Bringolf et al, 2007;Mann and Bidwell, 1999), but several studies have shown that commercial formulations containing glyphosate are more toxic than glyphosate alone due to the addition of surfactants (Folmar et al, 1979;Mann and Bidwell, 1999;Tsui and Chu, 2003). The most common adjuvants in glyphosate-based formulations are polyethoxylated tallow amines (POEAs) in the proportion of 10-20% (Howe et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…POEAs are diethoxylates of tallow amines that are characterised by the ratio of oxide: tallow-amine, which ranges from 5:1 to 25:1 . Although adjuvants are considered biologically inert by manufacturers and protection agencies, various studies have demonstrated that POEAs are toxic to aquatic organisms such as Daphnia magna , the freshwater fairy shrimp Thamnocephalus platyurus , the freshwater mussel Lampsilis siliquoidea (Bringolf et al, 2007) and four amphibian species (Howe et al, 2004). A study by Mottier et al (2013) reported that Roundup ® formulations are more toxic to D-shaped and pediveliger larvae than glyphosate alone or its by-product, aminomethylphosphonic acid (AMPA).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate that commercial glyphosate formulations can be more toxic than pure glyphosate due to the toxicity or action of the surfactants used (Giesy et al 2000;Bringolf et al 2007). Other studies indicate that the polyethoxylated tallowamine (POEA) surfactant (MON0818), used in some glyphosate formulations, is the principal toxicant responsible for effects on fish and amphibians (Edginton et al 2004;Folmar et al 1979;Perkins et al 2000; Thompson et al 2004).…”
Section: Introductionmentioning
confidence: 99%